Giant Parathyroid Adenoma - Jayant, M; Kaushik, R; Kochar, S; Attri, A K (Kathmandu University Medical Journal, 2012)
Primary Hyperparathyroidism is most commonly caused by parathyroid adenoma. Parathyroid adenoma is generally suspected by certain symptoms and biochemical abnormalities. They rarely attain large size to be evident clinically. We report a rare case of giant parathyroid adenoma measuring 5x4x3cm and weighing 35 gm. http://dx.doi.org/10.3126/kumj.v9i1.6269 Kathmandu Univ Med J 2011;9(1):77-9